2023
DOI: 10.3390/dj12010004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Intra-Operative and Post-Operative Pain Associated with Routine Dental Procedures in Children: A Systematic Review and Meta-Analysis

Mohammed A. Alzubaidi,
Bernadette K. Drummond,
Jianhua Wu
et al.

Abstract: Background: Understanding predictors of pain associated with paediatric dental procedures could play an important role in preventing loss of cooperation, which often leads to the procedure having to be performed under general anaesthesia. Aim: We aimed to identify predictors of intra-operative and post-operative pain associated with routine dental procedures in children. Materials and Methods: A systematic review of observational studies was performed using electronic searches on MEDLINE, EMBASE, PsycINFO, Glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…For instance, Ghanei et al (2018) reported that dental injection and extraction in children (aged 3 to 19 years) emerged as the most common causes of pain in paediatric dentistry, while drilling has been recognised as the second most common source of pain [ 6 ]. This is in agreement with a recent systematic review which showed extractions being the most painful dental procedure, followed by drilling [ 7 ]. Other studies considered dental injection as the procedure causing the highest pain [ 8 , 9 , 10 ].…”
Section: Introductionsupporting
confidence: 93%
“…For instance, Ghanei et al (2018) reported that dental injection and extraction in children (aged 3 to 19 years) emerged as the most common causes of pain in paediatric dentistry, while drilling has been recognised as the second most common source of pain [ 6 ]. This is in agreement with a recent systematic review which showed extractions being the most painful dental procedure, followed by drilling [ 7 ]. Other studies considered dental injection as the procedure causing the highest pain [ 8 , 9 , 10 ].…”
Section: Introductionsupporting
confidence: 93%